Contribuição ao estudo da imprimação betuminosa das bases rodoviárias do Estado do Ceará - Rabêlo, Antonio Nobre (2006)
Bituminous prime coat can be defined as the application of an asphalt film layer on a granular base, for the improvement of its technological qualities. In pavements subjected to the role of the prime coats is even more important due to the reduced thickness of the surface and its low or inexistent structural function. The purpose os this work is to investigate the main factors that affect the penetration of the bituminous prime coat in bases layers with traffic low volume in the state of Ceará. Soil samples were collected in the agrozone of Baixo Jaguaribe. This region was selected because of importance in the economic and social scene of the state. The collected samples were submitted to characterization tests, gradation, Proctor, CBR and expansion considering the intermediate energy. An adaptation of the compacting process was done for preparing the samples submitted to the prime coat tests. The change in the procedure consisted in compacting through the Marshall cylinder, instead of the Proctor cylinder. The procedures of the Villibor’s methodology were adapted, as well. The bituminous materials used in the prime coat tests were the emulsion RM-1C and cutback CM-30. It was also used a binder produced with the addition of the liquid of the cashew nut (LCC) to the asphalt cement. Results observed of the experiments had disclosed that the prime coat is a complex material, it’s affect by many factors, such as: the type and the rate the applied binder, the preparing conditions of the base surface, moisture content in compaction, etc. It was also verified that the LCC can satisfactorily be used as cutback, observing the parameter of penetration.